A broad climatology of very high latitude substorms - Singh, Anand K.; Sinha, Ashwini K.; Rawat, Rahul; Jayashree, B.; Pathan, B.M.; Dhar, Ajay (2012)
Magnetic data from a newly commissioned Indian Antarctic station Bharati (corrected geomagnetic (CGM) coordinates 74.7°S, 97.2°E) and closely-spaced IMAGE chain observatories (∼100° magnetic meridian in Northern hemisphere) has been analyzed to study the climatology of substorms which were localized poleward of the standard auroral oval. We considered four austral summers (year 2007–2010) when data from Bharati was available. Several very high latitude substorms were observed in this duration when the solar activity remained unexpectedly low for a long time. Various features of very high latitude substorms, e.g., local time dependence, interplanetary state, hemispherical asymmetry and their nightside low latitude signatures are examined. Events studied here, suggested the following properties of substorms occurring at very high latitudes: (1) maximum occurrence was observed near magnetic midnight (21:00–02:00 MLT). (2) In contradiction to earlier reports, many substorms were observed even during negative IMF Bz condition. In addition, majority of substorms occurred during low or moderate solar wind streams. (3) Magnetic signatures were often pronounced in the winter hemisphere. (4) Even if widely used standard AE indices fail to monitor very high latitude substorms, their low latitude signatures are often evident.